THE PARADOX OF POWER AND "SUBMISSION" OF WOMEN IN AFRICAN TRADITIONAL RELIGION AND SOCIETY - Onunwa, Udobata (Journal of Dharma, 1988)
Although it is true that in most African societies, male supremacy is taken for granted (just as in most societies in the world) it would be wrong to see the traditional African woman as a mere passive object in the practice of her religion. A spate of literature now exists on her role as either a priest, prophet, diviner etc. in the traditional religion.! One significant observation in most of the literature is that the writers do not attribute the freedom and independence which many African women enjoy, entirely to western influences. They therefore indirectly ascribe the freedom ontologically to the nature of African society. However the overt manifestation of some aspects of this freedom and 'power' has been submerged in several ways by a number of factors. That woman have "inherent mystical powers" in the belief and practice of African Traditional Religion and in society in general, is yet to be realised and understood by those still plagued by the bogey of 'male domination'.